Применение метода case-study в обучении профессионально- ориентированному общению на иностранном языке студентов-менеджеров - Бурлай, Н.В. (Культура народов Причерноморья, 2013)
В данной статье рассматриваются некоторые аспекты практического применения метода case-study для обучения профессионально-ориентированному общению на иностранном языке студентов-менеджеров. Метод case-study позволяет практиковать все виды речевой деятельности на иностранном языке, развивать коммуникативные, аналитические, творческие, управленческие навыки и углублять знания студентов по специальности. Кейсы и ролевые игры, рассматривающие проблемные ситуации реального бизнеса, мотивируют студентов-менеджеров изучать иностранный язык и применять на практике свои профессиональные знания. У даній статті розглядаються деякі аспекти практичного застосування методу case-study для навчання професійно-орієнтованому спілкуванню іноземною мовою студентів-менеджерів. Метод case-study дозволяє практикувати всі види мовної діяльності іноземною мовою, розвивати комунікативні, аналітичні, творчі, управлінські навички й поглиблювати знання студентів за фахом. Кейси й рольові ігри, що розглядають проблемні ситуації реального бізнесу, мотивують студентів- менеджерів вивчати іноземну мову й застосовувати на практиці свої професійні знання. The article presents some aspects of practical use of the case-study method in teaching profession- oriented foreign language communication to future managers. It deals with the teaching potential and advantages of the case-study method as an interactive teaching approach. The paper considers the process of learning the Business foreign language through analyzing case studies, supplemented by corresponding business role plays. It gives a general description of the structure of units included in the Business English course-book «Market Leader» and teaching tips concerning the stages of work on case studies. Recommendations given in the teacher’s book can be supplemented by different additional tasks according to the language competence of a particular group of students.